Interactions among the human and organizational factors within the public sector regarding epidemic prevention and control. Issue 1 (14th January 2022) - Fu, Lipeng; Wang, Xueqing; Deng, Shuyi; Cao, Shaopeng; Zhao, Heng
Abstract: The management of human and organizational factors (HOFs) within the public sector directly concerns the efficacy of epidemic prevention and control (EPC). Insufficient examination of such HOFs has led to defective countermeasures. This study attempts to comprehensively identify the HOFs within the public sector critical to EPC and investigate their interactions with the weighted network theory. A total of 55 HOFs were identified, and their interactions were assessed and visualized in the Chinese context. Then, the established weighted network was analyzed to investigate the interactions and diagnose critical factors and sectors. The analysis shows that there are strong interactions among HOFs, and that the human and organizational risks emerging from administrative departments of public health, centers for disease control and prevention, and medical institutions act as the key risk sources in the complex interconnected EPC system, exacerbating risk and causing a significant domino effect. It is recommended that the authorities devote more resources to the core sectors and endeavor to reinforce those critical HOFs by implementing closer risk communication, collaboration, and response. This study may deepen and broaden the authorities' awareness and understanding of interactions among HOFs regarding epidemic mitigation, and strengthen their capacity to perceive, evaluate, and manage these factors in a proactive and effective way, thereby facilitating the success of EPC.